Alkyne‐Substituted N‐Heterophenes. Issue 34 (22nd May 2017) - Hahn, Sebastian; Koser, Silke; Hodecker, Manuel; Tverskoy, Olena; Rominger, Frank; Dreuw, Andreas; Bunz, Uwe H. F.
Abstract: The synthesis and characterization of novel S‐shaped N‐heterophenes is reported. The targets contain a central anthracene connected to two heterophenanthrene units. N‐Heterophenes are synthesized by reacting Boldt's 1, 2, 6, 7‐anthracenetetraone with different dialkynylated ortho ‐diaminobenzenes. The condensation yields range from 63 to 75 %; all of the N‐heterophenes are stable and isolable. Abstract : S‐Express : The efficient synthesis of four different S‐shaped N‐heterophenes by condensation of aromatic ortho ‐diamines with 1, 2, 6, 7‐anthracenetetraone is reported. The optical and electronic properties of the targets were evaluated and their properties are discussed through comparisons with computational studies.